Analisis Kualitas Layanan Aplikasi WONDR by BNI Terhadap Kepuasan Nasabah (Studi Kasus Bank BNI KCP Paiton): Analisis Kualitas Layanan, Kepuasan Nasabah Terhadap Aplikasi WONDR by BNI, Bank BNI KCP Paiton - Hamzah, Muh; Paulia, Daud Em; Shofi, Ahmad; Efendi, Jauhari (LP2M IBK Nitro, 2025)
Digitalization in the banking sector drives transformation to meet customers' needs for fast, easy, and secure services. This study aims to evaluate the service quality of the WONDR application at Bank BNI KCP Paiton using a qualitative-descriptive approach. Data were collected through observations, interviews, and documentation. The findings reveal that the WONDR application offers innovative features such as QRIS payments, investments, and account opening, facilitating customer transactions. Customers provided positive feedback regarding the ease, speed, and security of the services. Despite challenges like limited network access, lack of education, and market competition, customer satisfaction remains high. This application plays a crucial role in enhancing transaction efficiency, customer experience, and loyalty to digital banking services. This study provides insights for BNI in formulating more effective strategies for digital service development in the future